High-strength heat-resistant green concrete and preparation method thereof
By using specific combinations of raw materials and modified materials, the compressive strength and heat resistance of heat-resistant concrete have been improved, solving the problems of insufficient strength and easy cracking at high temperatures in traditional heat-resistant concrete, and enabling high-performance applications in high-temperature environments.
Patent Information
- Application Number
- CN202411239527.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-10
AI Technical Summary
Existing heat-resistant concrete has low compressive strength, limited heat resistance, and poor crack resistance, especially prone to cracking at high temperatures, making it difficult to meet the requirements of high-strength applications.
A specific combination of raw materials is used, including cement, sand, crushed stone, fly ash, silica fume, water, water-reducing agent, activator, defoamer, shrinkage reducer and steel fiber, and titanate coupling agent modified glass microspheres and graphene modified potassium titanate whiskers are added to improve the interfacial bonding performance, strength and heat resistance of concrete through surface modification and uniform dispersion.
It significantly improves the compressive strength of concrete, maintains good heat resistance and structural stability at temperatures up to 1000℃, reduces the risk of cracking, and provides a better high-performance engineering option for high-temperature environments.
Smart Images

Figure BDA0005028814510000091 
Figure BDA0005028814510000101 
Figure BDA0005028814510000102
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building material technology, and in particular to a high-strength heat-resistant green concrete and a preparation method thereof. Background Art
[0002] Heat-resistant concrete is a special type of concrete designed for use in high-temperature environments ranging from 200°C to 900°C, and is able to maintain the required physical and mechanical properties and volume stability under these extreme conditions. This type of concrete is mainly used in thermal equipment, industrial kilns and other structures that need to withstand high temperatures, such as furnace walls, furnace pits, chimney linings and foundations. Its production process is relatively simple, the construction efficiency is high, and it can easily adapt to the construction needs of various shapes and parts.
[0003] In recent years, with the increasing application of concrete in non-standard temperature environments, people have begun to pay more attention to the changes in its mechanical properties at different temperatures. Current heat-resistant concrete is mainly based on ordinary concrete to improve heat resistance, but with the expansion of its application scope, traditional heat-resistant concrete has been difficult to meet actual needs, especially for applications that require higher strength. The compressive strength of traditional heat-resistant concrete can only reach the C30 to C40 level. Although high-strength concrete has higher strength, it is prone to cracking after high-temperature heating, especially when the temperature exceeds 400°C. Its residual strength will drop rapidly and fail at temperatures above 600°C. This shows that there is an urgent need in the market for a new type of concrete material that has both high strength and good heat resistance.
[0004] To meet this challenge, it is necessary to develop a high-strength heat-resistant concrete with a compressive strength higher than C40 and capable of withstanding temperatures up to 1000°C. Summary of the invention
[0005] In order to solve at least one of the above technical problems, a concrete with high compressive strength, good heat resistance and excellent crack resistance is developed. The present application provides a high-strength heat-resistant green concrete and a preparation method thereof. In a first aspect, the present application provides a high-strength heat-resistant green concrete, wherein the concrete comprises the following raw materials by weight: 600-750 parts of cement; Sand 1000-1250 parts; 1300-1450 parts of crushed stone; 130-150 parts of fly ash; Silica fume 65-85 parts; 180-200 parts of water; Water reducing agent 27-35 parts; 26-33 parts of stimulant; 6-10 parts of defoaming agent; Shrinkage reducing agent 21-29 parts; Steel fiber 20-28 parts; 30-50 parts of titanate coupling agent modified glass microspheres; 45-75 parts of graphene-modified potassium titanate whiskers.
[0006] By adopting the above technical scheme, in order to solve the problems of low compressive strength, limited heat resistance and poor crack resistance of existing heat-resistant concrete, the present application proposes a high-strength heat-resistant green concrete and its preparation method. The concrete adopts a specific combination of raw materials, including conventional components such as cement, sand, crushed stone, fly ash, silica fume, water, water reducer, activator, defoamer, shrinkage reducer and steel fiber, which work together to improve the basic strength and heat resistance of concrete. In particular, the present application adds two key materials, titanate coupling agent modified glass microspheres and graphene modified potassium titanate whiskers. Titanate coupling agent modified glass microspheres can better combine with the concrete matrix through surface modification, improve the interface bonding performance, improve the overall performance of concrete, and reduce the density of concrete and improve its thermal insulation performance. Graphene modified potassium titanate whiskers significantly improve the strength, heat resistance and thermal stability of concrete by being evenly dispersed in concrete. The addition of graphene can also enhance the microstructure of concrete and improve its density and crack resistance. Through the combination of these carefully designed components, the high-strength heat-resistant green concrete prepared not only has significantly improved compressive strength (higher than C40), but also maintains good heat resistance and structural stability at high temperatures up to 1000°C. In particular, the addition of titanate coupling agent-modified glass microspheres and graphene-modified potassium titanate whiskers further improves the comprehensive performance of concrete, enhances its crack resistance and overall durability, and reduces the risk of concrete cracking under high temperature. This solution solves the problems of insufficient strength of traditional heat-resistant concrete and easy cracking at high temperatures, providing a better choice for projects that need to maintain high performance in high temperature environments.
[0007] Optionally, the preparation method of the graphene-modified potassium titanate whiskers is as follows: S1: adding potassium titanate whiskers to sodium alginate solution at a weight ratio of 1:6, then adding hydrochloric acid to adjust the pH to 4.5-5.0, and then adding pentadecylphenol with a content of 25% of the total amount of potassium titanate whiskers, stirring thoroughly to obtain a potassium titanate whisker composite solution; S2: adding graphene to a sulfuric acid aqueous solution at a weight ratio of 1:6, stirring and dispersing the graphene evenly, and finally adding chitosan with a weight ratio of 25% of the total amount of graphene, stirring sufficiently, and obtaining a graphene agent; S3: Add the graphene agent into 35 times the potassium titanate whisker composite liquid, stir thoroughly, and finally wash and dry to obtain graphene-modified potassium titanate whiskers.
[0008] By adopting the above technical scheme, the preparation method of graphene-modified potassium titanate whiskers can significantly improve the strength, heat resistance and thermal stability of concrete. The addition of graphene can also enhance the microstructure of concrete, improve its density and crack resistance. In this way, the prepared high-strength heat-resistant green concrete not only has significantly improved compressive strength (higher than C40), but also maintains good heat resistance and structural stability at high temperatures up to 1000°C. In this way, the problems of insufficient strength of traditional heat-resistant concrete and easy cracking at high temperatures are solved, providing a better choice for projects that need to maintain high performance in high temperature environments.
[0009] Optionally, the preparation method of the titanate coupling agent modified glass microspheres is as follows: after mixing the hollow glass microspheres and the titanate coupling agent, a coupling reaction is carried out; after adding polyether glycol diglycidyl ether and mixing, dicyandiamide is added and a heat preservation reaction is carried out; after the heat preservation reaction is completed, the temperature is cooled to room temperature to obtain the titanate coupling agent modified hollow glass microspheres.
[0010] By adopting the above technical scheme, the present application proposes a high-strength heat-resistant green concrete, one of the key features of which is the use of titanate coupling agent modified glass microspheres. The preparation method of this modified glass microsphere is as follows: First, the hollow glass microspheres are mixed with the titanate coupling agent and a coupling reaction is carried out to improve the interfacial bonding performance between the glass microspheres and the concrete matrix. Subsequently, polyether glycol diglycidyl ether is added to the mixture to further promote the modification effect. Next, dicyandiamide is added to carry out a heat preservation reaction to ensure that the modification reaction is fully carried out. After the heat preservation reaction is completed, the mixture is cooled to room temperature to obtain hollow glass microspheres modified by a titanate coupling agent. This modified glass microsphere can not only improve the overall performance of concrete, but also reduce the density of concrete and improve its thermal insulation performance, so that the high-strength heat-resistant green concrete finally prepared not only has a significantly improved compressive strength (higher than C40), but also maintains good heat resistance and structural stability at high temperatures up to 1000°C.
[0011] Optionally, the weight ratio of the titanate coupling agent modified hollow glass microspheres to the graphene modified potassium titanate whiskers is 1:(1.3-1.8).
[0012] By adopting the above technical solution, this application can produce a synergistic effect by precisely controlling the weight ratio of hollow glass microspheres modified by titanate coupling agent and graphene modified potassium titanate whiskers, and the two modified materials can further improve the comprehensive performance of concrete. This synergistic effect not only improves the compressive strength of concrete (higher than C40), but also maintains good heat resistance and structural stability at high temperatures up to 1000°C. In particular, the addition of these two modified materials enhances the crack resistance and overall durability of concrete, and reduces the risk of concrete cracking under high temperature. In this way, the problems of insufficient strength of traditional heat-resistant concrete and easy cracking at high temperatures are solved, providing a better choice for projects that need to maintain high performance in high temperature environments.
[0013] Optionally, the weight ratio of the titanate coupling agent modified hollow glass microspheres to the graphene modified potassium titanate whiskers is 1:1.5.
[0014] Optionally, the total weight of the titanate coupling agent modified hollow glass microspheres and the graphene modified potassium titanate whiskers accounts for 2.5-3.2% of the total weight of the concrete.
[0015] Optionally, the cement is po42.5 cement.
[0016] Optionally, the water reducer is selected from high-efficiency polycarboxylate water reducer.
[0017] In a second aspect, the present application provides a method for preparing high-strength heat-resistant green concrete, the method for preparing the concrete comprising the following steps: S1, dividing water into four equal parts; and uniformly mixing the first part of water with cement, sand, crushed stone, fly ash, silica fume, hollow glass microspheres modified by titanate coupling agent, and graphene modified potassium titanate whiskers to prepare a first mixture; S2, the second portion of water is mixed with the activator, and the first portion of the mixture prepared in step S1 is added, and then the steel fiber is added and mixed evenly to prepare the second mixture. S3, mixing the third portion of water with the water reducing agent, adding the mixture to the second portion of the mixture and mixing evenly to obtain a third mixture; S4. Evenly mix the fourth portion of water with the defoamer and the shrinkage reducing agent, and add the mixture to the third portion of the mixture, mix evenly to obtain a concrete mixture, and cast and cure the concrete mixture to obtain high-strength heat-resistant green concrete.
[0018] By adopting the above technical solution, the present application proposes that through this step-by-step mixing method, each component can be fully dispersed and evenly mixed, ensuring the homogeneity of the concrete. In particular, the addition of hollow glass microspheres modified by titanate coupling agents and graphene-modified potassium titanate whiskers significantly improves the compressive strength of concrete (higher than C40), and maintains good heat resistance and structural stability at high temperatures up to 1000°C. This preparation method not only ensures the high strength and heat resistance of concrete, but also enhances its crack resistance and overall durability, and reduces the risk of concrete cracking under high temperature. In this way, the problems of insufficient strength of traditional heat-resistant concrete and easy cracking at high temperatures are solved, providing a better choice for projects that need to maintain high performance in high temperature environments.
[0019] Optionally, the curing is as follows: first, under the conditions of a temperature of 20-30°C and a humidity of 80-90%, the curing time is 7-10 days, and then under the conditions of a temperature of 23±2°C and a humidity of 50-60%, the curing time is at least 21 days.
[0020] In summary, the present invention includes at least one of the following beneficial technical effects: 1. In order to solve the problems of low compressive strength, limited heat resistance and poor crack resistance of existing heat-resistant concrete, this application proposes a high-strength heat-resistant green concrete and its preparation method. The concrete adopts a specific combination of raw materials, including conventional components such as cement, sand, crushed stone, fly ash, silica fume, water, water reducer, activator, defoamer, shrinkage reducer and steel fiber, which work together to improve the basic strength and heat resistance of concrete. In particular, this application adds two key materials, titanate coupling agent modified glass microspheres and graphene modified potassium titanate whiskers. Titanate coupling agent modified glass microspheres can better combine with the concrete matrix through surface modification, improve the interfacial bonding performance, improve the overall performance of concrete, and reduce the density of concrete and improve its thermal insulation performance. Graphene modified potassium titanate whiskers significantly improve the strength, heat resistance and thermal stability of concrete by being evenly dispersed in concrete. The addition of graphene can also enhance the microstructure of concrete, improve its density and crack resistance. Through the combination of these carefully designed components, the high-strength heat-resistant green concrete prepared not only has significantly improved compressive strength (higher than C40), but also maintains good heat resistance and structural stability at high temperatures up to 1000°C. In particular, the addition of titanate coupling agent-modified glass microspheres and graphene-modified potassium titanate whiskers further improves the comprehensive performance of concrete, enhances its crack resistance and overall durability, and reduces the risk of concrete cracking under high temperature. This solution solves the problems of insufficient strength of traditional heat-resistant concrete and easy cracking at high temperatures, providing a better choice for projects that need to maintain high performance in high temperature environments.
[0021] 2. The preparation method of graphene-modified potassium titanate whiskers can significantly improve the strength, heat resistance and thermal stability of concrete. The addition of graphene can also enhance the microstructure of concrete, improve its density and crack resistance. In this way, the prepared high-strength heat-resistant green concrete not only has significantly improved compressive strength (higher than C40), but also maintains good heat resistance and structural stability at high temperatures up to 1000°C. In this way, the problems of insufficient strength of traditional heat-resistant concrete and easy cracking at high temperatures are solved, providing a better choice for projects that need to maintain high performance in high temperature environments.
[0022] 3. The present application proposes a high-strength, heat-resistant green concrete, one of the key features of which is the use of titanate coupling agent modified glass microspheres. The preparation method of this modified glass microsphere is as follows: First, the hollow glass microspheres are mixed with the titanate coupling agent and a coupling reaction is carried out to improve the interfacial bonding performance between the glass microspheres and the concrete matrix. Subsequently, polyether glycol diglycidyl ether is added to the mixture to further promote the modification effect. Next, dicyandiamide is added and a heat preservation reaction is carried out to ensure that the modification reaction is fully carried out. After the heat preservation reaction is completed, the mixture is cooled to room temperature to obtain hollow glass microspheres modified by a titanate coupling agent. This modified glass microsphere can not only improve the overall performance of the concrete, but also reduce the density of the concrete and improve its thermal insulation performance, so that the high-strength, heat-resistant green concrete finally prepared not only has a significantly improved compressive strength (higher than C40), but also maintains good heat resistance and structural stability at high temperatures up to 1000°C. DETAILED DESCRIPTION
[0023] The present application is further described in detail below in conjunction with embodiments.
[0024] po42.5 cement: Taizhou Yigao E-Commerce Co., Ltd.
[0025] Preparation Example 1 The preparation method of graphene-modified potassium titanate whiskers is as follows: S1: adding potassium titanate whiskers to a sodium alginate solution at a weight ratio of 1:6, then adding hydrochloric acid to adjust the pH to 4.5, and then adding 2% of pentadecylphenol to the total amount of potassium titanate whiskers, stirring thoroughly to obtain a potassium titanate whisker composite solution; S2: adding graphene to a sulfuric acid aqueous solution at a weight ratio of 1:6, stirring and dispersing the graphene evenly, and finally adding chitosan at a weight ratio of 2% of the total amount of graphene, stirring sufficiently, and obtaining a graphene agent; S3: Add the graphene agent into 3 times the potassium titanate whisker composite liquid, stir thoroughly, and finally wash and dry to obtain graphene-modified potassium titanate whiskers.
[0026] Preparation Example 2 The preparation method of graphene-modified potassium titanate whiskers is as follows: S1: adding potassium titanate whiskers to a sodium alginate solution at a weight ratio of 1:6, then adding hydrochloric acid to adjust the pH to 5.0, and then adding 4% of pentadecylphenol to the total amount of potassium titanate whiskers, stirring thoroughly to obtain a potassium titanate whisker composite solution; S2: adding graphene to a sulfuric acid aqueous solution at a weight ratio of 1:6, stirring and dispersing the graphene evenly, and finally adding chitosan with a total amount of 4.5% of the graphene, stirring sufficiently, and obtaining a graphene agent; S3: Add the graphene agent to 4.5 times the potassium titanate whisker composite liquid, stir thoroughly, and finally wash and dry to obtain graphene-modified potassium titanate whiskers.
[0027] Preparation Example 3 The preparation method of graphene-modified potassium titanate whiskers is as follows: S1: adding potassium titanate whiskers to a sodium alginate solution at a weight ratio of 1:6, then adding hydrochloric acid to adjust the pH to 5.0, and then adding 5% of pentadecylphenol to the total amount of potassium titanate whiskers, stirring thoroughly to obtain a potassium titanate whisker composite solution; S2: adding graphene to a sulfuric acid aqueous solution at a weight ratio of 1:6, stirring and dispersing the graphene evenly, and finally adding chitosan at a weight ratio of 5% of the total amount of graphene, stirring sufficiently, and obtaining a graphene agent; S3: Add the graphene agent into 5 times the potassium titanate whisker composite liquid, stir thoroughly, and finally wash and dry to obtain graphene-modified potassium titanate whiskers. Specific embodiments
[0028] Example 1 The present embodiment provides a high-strength, heat-resistant green concrete, which includes the following raw materials by weight: 600 parts of cement; 1000 parts of sand; 1300 parts of crushed stone; 130 parts of fly ash; 65 parts of silica fume; 180 parts of water; 27 parts of water reducer; 26 parts of activator; 6 parts of defoamer; 21 parts of shrinkage reducer; 20 parts of steel fiber; 40 parts of glass microspheres modified with titanate coupling agent; and 60 parts of graphene-modified potassium titanate whiskers.
[0029] The graphene-modified potassium titanate whiskers in this preparation example are prepared by Preparation Example 1.
[0030] The preparation method of hollow glass microspheres modified by titanate coupling agent is as follows: 40.7 parts by weight (g) of hollow glass microspheres with a particle size of 25 microns are put into a stirrer at a speed of 800 r / min, and the temperature is raised to 110°C while stirring. The mixture is heated for 1.5 hours to dry the surface moisture. 0.1 parts of titanate coupling agent are added to the stirrer, and then the speed is maintained at 800 r / min. After the mixture is kept at 110°C for reaction for 30 minutes, the speed is maintained to cool to 80°C, and then 0.9 parts by weight of polyether glycol diglycidyl ether is added by spraying while stirring. After the mixture is kept at 80°C and stirred for 60 minutes, 0.3 parts by weight of dicyandiamide are added. After the mixture is kept at 80°C and stirred for 1 hour, the mixture is cooled to room temperature with stirring. The material is discharged and sealed for storage to obtain modified hollow glass microspheres.
[0031] The cement in this embodiment is po42.5 cement. The particle size of the crushed stone in this embodiment is that the crushed stone is selected from limestone and basalt crushed stone with good gradation, compactness, hardness and rough surface in a mass ratio of 1:1, and the particle size range is 5mm15mm. The crushed stones of continuous particle size of 510mm and 1015mm are mixed in a mass ratio of 5:5. The water reducer in this embodiment is a high-efficiency polycarboxylic acid water reducer. The activator in this embodiment is calcium chloride. The defoamer in this embodiment is a defoamer of Datian Chemical, model PT-5230. The shrinkage reducer in this embodiment is a P80 high-efficiency shrinkage reducer. The length of the ramie fiber in this embodiment is 4050mm and the diameter is 30μm40μm. The length of the steel fiber in this embodiment is 12mm and the diameter is 7μm15μm.
[0032] The sand is made of hard river sand and well-graded high-quality quartz sand with a mass ratio of 8:2. The river sand fineness modulus is 2.83.0, the silica content in the quartz sand is not less than 98%, the particle size is 0.30.6mm, and the density is 2.62g / cm 3 .
[0033] The method for preparing concrete in this embodiment comprises the following steps: S1, dividing water into four equal parts; and uniformly mixing the first part of water with cement, sand, crushed stone, fly ash, silica fume, hollow glass microspheres modified by titanate coupling agent, and graphene modified potassium titanate whiskers to prepare a first mixture; S2, the second portion of water is mixed with the activator, and the first portion of the mixture prepared in step S1 is added, and then the steel fiber is added and mixed evenly to prepare the second mixture. S3, mixing the third portion of water with the water reducing agent, adding the mixture to the second portion of the mixture and mixing evenly to obtain a third mixture; S4. Evenly mix the fourth portion of water with the defoamer and the shrinkage reducing agent, and add the mixture to the third portion of the mixture, mix evenly to obtain a concrete mixture, and cast and cure the concrete mixture to obtain high-strength heat-resistant green concrete.
[0034] The curing is as follows: first, at a temperature of 30°C and a humidity of 90%, the curing time is 8 days, and then at a temperature of 23±2°C and a humidity of 60%, the curing time is 24 days.
[0035] Example 2 The difference between this embodiment and embodiment 1 is that when preparing high-strength heat-resistant green concrete, the total weight of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers is 100 parts, and the weight ratio of the hollow glass microspheres modified by the titanate coupling agent to the graphene-modified potassium titanate whiskers is 1:1.3.
[0036] Example 3 The difference between this embodiment and embodiment 1 is that when preparing high-strength heat-resistant green concrete, the total weight of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers is 100 parts, and the weight ratio of the hollow glass microspheres modified by the titanate coupling agent to the graphene-modified potassium titanate whiskers is 1:1.6.
[0037] Example 4 The difference between this embodiment and embodiment 1 is that when preparing high-strength heat-resistant green concrete, the total weight of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers is 100 parts, and the weight ratio of the hollow glass microspheres modified by the titanate coupling agent to the graphene-modified potassium titanate whiskers is 1:1.8.
[0038] Comparative Examples 1-3 Comparative Example 1 The difference between this comparative example and Example 1 is that when preparing the high-strength heat-resistant green concrete, an equal amount of hollow glass microspheres modified by a titanate coupling agent are used instead of graphene-modified potassium titanate whiskers.
[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that when preparing the high-strength heat-resistant green concrete, an equal amount of graphene-modified potassium titanate whiskers is used to replace the titanate coupling agent-modified hollow glass microspheres.
[0040] Comparative Example 3 The difference between this comparative example and Example 1 is that, when preparing the high-strength heat-resistant green concrete, an equal amount of potassium titanate whiskers is used instead of graphene-modified potassium titanate whiskers.
[0041] Experimental testing: 1. Compressive strength: According to GB / T500812019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength of the sample is tested.
[0042] Heat resistance test: The concrete prepared in Implementation Example 1-4 and the concrete prepared in the comparative example were made into cubic test blocks with a side length of 500 mm. After standard curing for 28 days, they were taken out and dried naturally, and cut into 100 mm×100 mm×100 mm samples. They were tested for 3 hours at different high temperature ranges, with a heating rate of 10°C / min. After that, the furnace door was opened and naturally cooled to room temperature to test the compressive strength of the concrete test blocks. The number of cracks on the surface of the cube was observed and recorded by naked eyes, and the temperature at which the cracks began to appear was recorded. The high temperature range is 900+10n°C (n is an integer of 0-40).
[0043] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.
[0044] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3 Example Compressive strength (28d) Heat resistance(℃) Example 1 105.4 1110 Example 2 102.5 1060 Example 3 104.1 1090 Example 4 103.8 1080 Comparative Example 1 96.3 940 Comparative Example 2 98.1 980 Comparative Example 3 90.4 900 Result analysis: The difference between Examples 2-4 and Example 1 is that when preparing high-strength heat-resistant green concrete, the weight ratio of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers is different. Combined with the experimental test data in Table 1, it can be seen that when the weight ratio of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers is 1:1.5, the comprehensive performance of the high-strength heat-resistant green concrete obtained is better. The difference between Comparative Example 1 and Example 1 is that when preparing high-strength heat-resistant green concrete, the same amount of hollow glass microspheres modified by the titanate coupling agent are used to replace the graphene-modified potassium titanate whiskers. The difference between Comparative Example 2 and Example 1 is that when preparing high-strength heat-resistant green concrete, the same amount of graphene-modified potassium titanate whiskers are used to replace the hollow glass microspheres modified by the titanate coupling agent. It can be seen from the experimental test data in Table 1 that when graphene-modified potassium titanate whiskers and titanate coupling agent-modified hollow glass microspheres are used simultaneously, the compressive strength and heat resistance of concrete are significantly improved. The difference between Comparative Example 3 and Example 1 is that when preparing high-strength heat-resistant green concrete, an equal amount of potassium titanate whiskers are used instead of graphene-modified potassium titanate whiskers. It can be seen from the experimental test data in Table 1 that when unmodified sepiolite is used, the compressive strength and heat resistance of concrete are affected. The reason may be that the interface bonding performance between unmodified potassium titanate whiskers and the concrete matrix is poor, which will cause the overall performance of concrete to decline. Graphene modification can improve the compatibility and interface bonding performance between potassium titanate whiskers and the concrete matrix, thereby significantly improving the compressive strength and heat resistance of concrete. In summary, by precisely controlling the weight ratio of titanate coupling agent-modified hollow glass microspheres and graphene-modified potassium titanate whiskers and using these two modified materials at the same time, the compressive strength and heat resistance of concrete can be significantly improved, thus providing a better choice for projects that need to maintain high performance in high temperature environments.
[0045] Embodiment 5-6 The difference between Example 5-6 and Example 1 is that when preparing the high-strength heat-resistant green concrete, the weight percentages of some components are changed. The differences are shown in Table 2.
[0046] Table 2 - Differences between Example 5-6 and Example 1 The experimental test results of Examples 5-6 are shown in Table 3.
[0047] Table 3 - Experimental test results of Examples 5-6 Example Compressive strength (28d) Heat resistance(℃) Example 1 105.4 1110 Example 5 107.9 1140 Example 6 106.2 1120 Result analysis: The difference between Example 5-6 and Example 1 is that when preparing the high-strength heat-resistant green concrete, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the high-strength heat-resistant green concrete prepared by Example 5 is better.
[0048] Embodiment 7-11 The difference between Example 7-11 and Example 5 is that when preparing high-strength heat-resistant green concrete, on the premise that the weight ratio of hollow glass microspheres modified by titanate coupling agent and graphene modified potassium titanate whiskers is 1:1.5, the total weight ratio of hollow glass microspheres modified by titanate coupling agent and graphene modified potassium titanate whiskers in the high-strength heat-resistant green concrete is changed, and the optimal weight ratio is selected.
[0049] In Example 5, the total weight of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers is 100 parts, and the total weight of the high-strength heat-resistant green concrete is 3940 parts.
[0050] Therefore, it is not difficult to conclude that in Example 5, the proportion of the hollow glass microspheres modified by the titanate coupling agent (referred to as variable 1) and the graphene-modified potassium titanate whiskers (referred to as variable 2) in the high-strength heat-resistant green concrete (referred to as the matrix) is 2.54%.
[0051] The differences between Examples 7-11 and Example 5 are shown in Table 4.
[0052] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.
[0053] Table 4 - Differences between Examples 7-11 and Example 5 The experimental test results of Examples 7-11 are shown in Table 5.
[0054] Table 5 - Experimental test results of Examples 7-11 Example Compressive strength (28d) Heat resistance(℃) Example 5 107.9 1140 Example 7 105.5 1120 Example 8 106.6 1130 Example 9 108.2 1160 Example 10 109.9 1190 Embodiment 11 109.0 1170 Result analysis: The difference between Example 7-11 and Example 5 is that when preparing high-strength heat-resistant green concrete, the total weight of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers in the high-strength heat-resistant green concrete is different. Combined with the experimental test results in Table 5, it can be seen that when the total weight of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers in the high-strength heat-resistant green concrete accounts for 2.54-3.1, the comprehensive performance of the obtained high-strength heat-resistant green concrete is better, and when the total weight of the hollow glass microspheres modified by the titanate coupling agent and the graphene-modified potassium titanate whiskers in the high-strength heat-resistant green concrete accounts for about 3%, the comprehensive performance of the obtained high-strength heat-resistant green concrete is the best. When the proportion is too high or too low, the comprehensive performance is reduced.
[0055] Examples 12-13 Example 12 The difference between this embodiment and embodiment 10 is that when preparing high-strength heat-resistant green concrete, the preparation parameters of the graphene-modified potassium titanate whiskers used are different. The graphene-modified potassium titanate whiskers in this embodiment are prepared by Preparation Example 2.
[0056] Example 13 The difference between this embodiment and embodiment 10 is that when preparing high-strength heat-resistant green concrete, the preparation parameters of the graphene-modified potassium titanate whiskers used are different. The graphene-modified potassium titanate whiskers in this embodiment are prepared by Preparation Example 3.
[0057] Table 6 - Experimental test results of Examples 12-13 Example Compressive strength (28d) Heat resistance(℃) Example 10 109.9 1190 Example 12 111.4 1210 Example 13 110.2 1200 Result analysis: The difference between Examples 12-13 and Example 10 is that different preparation parameters of graphene-modified potassium titanate whiskers are used in preparing high-strength heat-resistant green concrete. Combined with the experimental test results in Table 6, it can be seen that the high-strength heat-resistant green concrete prepared by Example 12 has better comprehensive performance.
[0058] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A high-strength heat-resistant green concrete, characterized in that: The concrete comprises the following raw materials by weight: 600-750 parts of cement; Sand 1000-1250 parts; 1300-1450 parts of crushed stone; Fly ash 130-150 parts; Silica fume 65-85 parts; 180-200 parts of water; Water reducing agent 27-35 parts; 26-33 parts of stimulant; 6-10 parts of defoaming agent; Shrinkage reducing agent 21-29 parts; Steel fiber 20-28 parts; 30-50 parts of titanate coupling agent modified glass microspheres; 45-75 parts of graphene-modified potassium titanate whiskers.
2. A high-strength heat-resistant green concrete according to claim 1, characterized in that: The preparation method of the graphene-modified potassium titanate whisker is as follows: S1: adding potassium titanate whiskers to sodium alginate solution at a weight ratio of 1:6, then adding hydrochloric acid to adjust the pH to 4.5-5.0, and then adding pentadecylphenol with a content of 25% of the total amount of potassium titanate whiskers, stirring thoroughly to obtain a potassium titanate whisker composite solution; S2: adding graphene to a sulfuric acid aqueous solution at a weight ratio of 1:6, stirring and dispersing the graphene evenly, and finally adding chitosan with a weight ratio of 25% of the total amount of graphene, stirring sufficiently, and obtaining a graphene agent; S3: Add the graphene agent into 35 times the potassium titanate whisker composite liquid, stir thoroughly, and finally wash and dry to obtain graphene-modified potassium titanate whiskers.
3. The high-strength heat-resistant green concrete according to claim 1, characterized in that: The preparation method of the titanate coupling agent modified glass microspheres is as follows: hollow glass microspheres and titanate coupling agents are mixed, and then coupling reaction is carried out; polyether glycol diglycidyl ether is added and mixed, and then dicyandiamide is added and heat preservation reaction is carried out; after the heat preservation reaction is completed, the temperature is cooled to room temperature to obtain the titanate coupling agent modified hollow glass microspheres.
4. The high-strength heat-resistant green concrete according to claim 1, characterized in that: The weight ratio of the titanate coupling agent modified hollow glass microspheres to the graphene modified potassium titanate whiskers is 1:(1.3-1.8).
5. The high-strength heat-resistant green concrete according to claim 4, characterized in that: The weight ratio of the titanate coupling agent modified hollow glass microspheres to the graphene modified potassium titanate whiskers is 1:1.
5.
6. The high-strength heat-resistant green concrete according to claim 1, characterized in that: The total weight of the titanate coupling agent modified hollow glass microspheres and the graphene modified potassium titanate whiskers accounts for 2.5-3.2% of the total weight of the concrete.
7. The high-strength heat-resistant green concrete according to claim 1, characterized in that: The cement is po42.5 cement.
8. The high-strength heat-resistant green concrete according to claim 1, characterized in that: The water reducer is selected from high-efficiency polycarboxylate water reducer.
9. A method for preparing the high-strength heat-resistant green concrete according to any one of claims 1 to 8, characterized in that: The method for preparing the concrete comprises the following steps: S1, dividing water into four equal parts; and uniformly mixing the first part of water with cement, sand, crushed stone, fly ash, silica fume, hollow glass microspheres modified by titanate coupling agent, and graphene modified potassium titanate whiskers to prepare a first mixture; S2, the second portion of water is mixed with the activator, and the first portion of the mixture prepared in step S1 is added, and then the steel fiber is added and mixed evenly to prepare the second mixture. S3, mixing the third portion of water with the water reducing agent, adding the mixture to the second portion of the mixture and mixing evenly to obtain a third mixture; S4. Evenly mix the fourth portion of water with the defoamer and the shrinkage reducing agent, and add the mixture to the third portion of the mixture, mix evenly to obtain a concrete mixture, and cast and cure the concrete mixture to obtain high-strength heat-resistant green concrete.
10. The method for preparing high-strength heat-resistant green concrete according to claim 9, characterized in that: The curing is as follows: first, the curing time is 7-10 days under the conditions of temperature of 20-30°C and humidity of 80-90%, and then the curing time is at least 21 days under the conditions of temperature of 23±2°C and humidity of 50-60%.
Citation Information
Cited By
High-strength low-shrinkage concrete based on inorganic filler and preparation method thereof
CN122482769A